Eye donation awareness among medical and paramedical staff in a medical institute - Arya, Sudesh Kumar; Gupta, Neeti; Malik, Archana (Nepalese Journal of Ophthalmology, 2014)
Introduction: Corneal diseases constitute a significant cause of visual impairment and blindness in the developing world. The number of corneal transplants done is far less than required due to the lack of donor cornea. A well informed and motivated medical and paramedical staff can increase the rate of eye donation by counseling grief-stricken relatives of the deceased for eye donation. Objective: To assess the awareness of the medical and paramedical staff of a medical institute about eye donation. Materials and methods: This was a cross-sectional study. A self-designed, standardized, single-response type questionnaire on eye donation awareness was prepared and circulated in all the departments of our institute. Results: Of the 395 participants, 317(80.5%) were aware of eye donation, 312(80%) knew that the cornea is used for eye donation and 294(76%) knew that the ideal time for eye donation is within six hours of death. Only 286(72.4%) knew about pledging for eye donation and only 251(65.4%) consented for pledge of their eyes. Of those who did not want to pledge, 12(14.8%) had religious reasons, 9(11.1%) feared disfigurement, 9(11.1%) thought that they might be born blind in their next birth and 51(63%) had some other reasons. Conclusion: There is a need for regular eye donation awareness programs not only in the community but even for the medical and paramedical staff in hospitals and medical colleges. This will ultimately enhance the eye donation program in the country to help cope with the backlog in the long term. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11700 Nepal J Ophthalmol 2014; 6(12): 177-184